Chandipura viral encephalitis: A re-emerging threat to public health and regional security in South Asia - Parmar, Rugved; Parihar, Ranjeet; Rebuma, Tesfaye; Pal, Mahendra (PT. Mega Science Indonesia, 2025)
Chandipura viral encephalitis (CHPV) has emerged as a significant public health challenge in South Asia, particularly in pediatric populations, with alarming mortality rates. This review synthesizes the current knowledge about the impact of CHPV on human health and healthcare systems. A comprehensive analysis of the published literature, outbreak reports, and clinical studies was conducted to evaluate the epidemiology, clinical manifestations, diagnostic approaches, and treatment strategies of CHPV. CHPV has a distinct predilection for children under 15 years of age, with case fatality rates ranging from 55–70% in severe pediatric cases. Disease progression is characterized by the rapid onset of symptoms, typically evolving from initial influenza-like manifestations to severe neurological complications within 48 h. The clinical presentations include high-grade fever, altered consciousness, seizures, and various neurological deficits. Diagnostic challenges persist, particularly in resource-limited settings, despite advances in molecular detection methods. Treatment remains primarily supportive, with a focus on managing severe complications and maintaining vital organ function. Socioeconomic impacts are substantial, with catastrophic healthcare costs affecting vulnerable populations and straining healthcare systems in endemic regions. The reemergence of CHPV poses serious challenges to public health systems, particularly in resource-limited settings. Rapid progression of the virus, high mortality rates, and significant socioeconomic burden necessitate enhanced surveillance systems, improved diagnostic capabilities, and strengthened healthcare infrastructure. The priority areas for intervention include developing point-of-care diagnostics, establishing standardized treatment protocols, and implementing sustainable vector control programs.